MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA - Hasibuan, Eka Khairani; Armanto, Dian; Amry, Zul (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research examines the effectiveness of Problem-Based Learning (PBL) in mathematics education through a systematic analysis of 27 research journals. The study focuses on the implementation of PBL in enhancing critical thinking abilities, problem-solving skills, mathematical literacy, as well as student motivation and learning outcomes. Meta-analysis results indicate that PBL has significant positive effects on critical thinking abilities in mathematics learning (g=0.769) and science (g=1.122). Comparative studies suggest that PBL is more effective than conventional learning in improving critical thinking skills and learning motivation. Several classroom action research studies report improvements in learning mastery and student mathematics achievement following PBL implementation. However, PBL implementation also faces challenges such as student passivity, teacher readiness, time management, and difficulties in achieving Higher Order Thinking Skills (HOTS) indicators. The development of PBL-based learning tools and interactive media shows promising results in enhancing learning effectiveness. This research concludes that PBL is an effective approach for developing higher-order thinking skills and conceptual understanding in mathematics, although its success depends on teacher readiness and adequate learning system support.